Dominant frequency predicts sinus rhythm maintenance after electrical cardioversion for persistent atrial fibrillation in men but not in women. (25th November 2020) - Lankveld, T; Zeemering, S; Van Gelder, I.C; Odening, K.E; Crijns, H.J; Schotten, U
Abstract: Background: Women are usually underrepresented in studies evaluating rhythm control strategies in patients with atrial fibrillation (AF). Subsequently, the same holds true for studies looking at predictors for success of a rhythm control strategy for AF. Purpose: To study the predictive power of the non-invasively determined dominant frequency (DF) on the electrocardiogram (ECG) in men and women undergoing electrical cardioversion (ECV) for persistent AF. Methods: We matched 105 female patients undergoing elective ECV for persistent AF and 105 male control patients based on age and cardiovascular comorbidity profile. We determined the DF on all 12 leads of a standard digital 10 seconds ECG recorded on the day of ECV. Recurrences of AF within the first year after ECV were documented. Results: There were no differences in comorbidities, AF duration, left ventricular systolic function, indexed left atrial volume and anti-arrhythmic drugs between male and female patients. The dominant frequency was significantly lower in male patients without an AF recurrence on all leads. The best performing lead to identify patients with recurrences was lead III with an AUC 0.752. The optimal cut-off point was a DF <5.98 Hz with a sensitivity 84% and a specificity 67%. There was no significant difference in DF between female patients with and without an AF recurrence. The AUC in lead III was 0.47 (Figure 1). Conclusion: The non-invasively measured dominant frequency is able to predict AF recurrence after electrical cardioversion in male patients with persistent AF but not in a matched female cohort. This difference might be explained by different pathophysiological mechanisms underlying AF in male and female patients. Therefore, future research is needed on pathophysiological differences between men and women that can explain and might overcome these challenges. Funding Acknowledgement: Type of funding source: Public grant(s) – EU funding. Main funding source(s): European Network for Translational Research in Atrial Fibrillation (grant no. 261057), the Center for Translational Molecular Medicine (COHFAR),